DESENVOLVIMENTO DE MÉTODO ELETROANALÍTICO PARA A DETERMINAÇÃO DO TEOR DE BIODIESEL NO DIESEL POR ESPECTROSCOPIA DE IMPEDÂNCIA ELETROQUÍMICA - Pereira, Thulio César (2014)
Due to the increasing integration of biodiesel into the national energy matrix, the determination of the content of this biofuel in the blend with diesel has become one of the most important parameters to ensure the quality standard of Diesel B (biodiesel-diesel blends), preventing damage caused by adding lower levels of biodiesel than those described for law or non-esterified oils instead biodiesel. A preliminary study carried out on this laboratory has indicated that a small teflon electrochemical cell carrying two electrodes 304 stainless steel positioned parallel a short distance was suitable for impedance measurements in the middle biodiesel. In this work, an electroanalytical method was developed for the determination of biodiesel in diesel using electrochemical impedance spectroscopy technique. The optimized instrumental conditions were the following: amplitude "rms" = 200 mV; frequency range = 100 kHz to 20 mHz; measurement points per decade = 10; nature of the measures = open circuit potential (OCP). The results demonstrated that the charge transfer resistance at the interface (Rct) showed a clear tendency to increase with the increase of the amount of biodiesel in the diesel / biodiesel blends. This behavior was related with the formation of a possible insulating film on the surface of the electrodes with capacitive characteristics, which hinder the passage of current, which was represented by constant phase element (CPE) in the proposed equivalent electrical circuit. The proposed procedure, based on this pronounced change in the resistance of charge transfer, was applied in two samples provided and previously analyzed by the LAPQAP / UFMA, whose results were validated statistically and compared with the results provided by the official method used by the ANP. The application of the Student t test showed no significant difference between the results obtained with the proposed method (sample 1 = 5.03% and sample 2 = 4.78%) and the official method (sample 1 = 4.90 % and sample 2 = 4.65 %) for a confidence level of 95%. The accuracy of the proposed method was checked by recovery tests in the 102, 6% to 102, 7% range. The precision was checked by the coefficient of variation (CV), which presented values lower than 2.3%. Values of 0.24% for the detection limit of and 0.80% for the limit of quantification, indicate a satisfactory sensitivity for the application of the method in the determination of the biodiesel in Dieesel content.